Teachers’ Perceptions around Digital Games for Children in Low-resource Schools for the Blind - India, Gesu; Y, Vidhya; O, Aishwarya; Diwakar, Nirmalendu; Jain, Mohit; Vashistha, Aditya; Manohar, Swami (CHI Conference on Human Factors in Computing Systems (CHI’21), 2021)
Most children who are blind live in low-resource settings and attend schools that have poor technical infrastructure, overburdened teachers, and outdated curriculum. Our work explores the role digital games can play to develop digital skills of such children in the early grades. Recognizing the critical role of teachers in introducing children to technology, we conducted a mixed-methods study to examine which attributes of digital games teachers find useful for children and what challenges they perceive in integrating digital games in schools for the blind. Our findings indicate that teachers prefer games that align well with curriculum objectives, promote learning, improve soft skills, and increase engagement with computers. Despite being overburdened and lacking technological support, teachers expressed strong enthusiasm to integrate these games in school curriculum and schedule. We conclude by discussing design implications for designers of accessible games in low-resource settings.